A new microwave-assisted, three-component reaction of 5-aminopyrazole-4-carboxylates: Selective synthesis of substituted 5-aza-9-deaza-adenines - Lim, F.; Halcovitch, N.; Tiekink, E.; Dolzhenko, Anton (Pergamon-Elsevier Science Ltd, 2018)
Â© 2018 Elsevier Ltd A series of 5-aza-9-deaza- analogues of purine was effectively prepared using highly selective annulation of 1,3,5-triazine ring onto 5-aminopyrazole-4-carboxylates via a one-pot, multicomponent, microwave-assisted approach. The products were obtained in good yields and high purity. This catalyst-free method was demonstrated to be scalable and highly reproducible in different microwave reactors. Some structural features of the prepared compounds were studied in details using dynamic NMR spectroscopy and X-ray crystallography.